2022
DOI: 10.31571/bahasa.v11i1.3528
|View full text |Cite
|
Sign up to set email alerts
|

Efl Students' Critical Thinking in Speaking Activities

Abstract: This research aimed to investigate how EFL students apply critical thinking in speaking activities and to explore the levels of critical thinking achieved by EFL students in speaking activities at e-COLINK Pontianak. The population of this research was the EFL students of advanced level 3 at e-COLINK Pontianak with a total of eight students. The samples of this research were selected using total sampling technique. The researcher applied the type of descriptive research with a qualitative approach. The techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Some focus on cultural incorporation (Ariawan, 2020;Elmiana, 2019;Setyono & Widodo, 2019), gender representation (Koster & Litosseliti, 2021;Lee, 2018;Sovič & Hus, 2015;Widodo & Elyas, 2020;Yasin et al, 2012), ideology, religion, and identity (Behnam & Mozaheb, 2013;Tran-Thanh, 2020;Vu & Febrianti, 2018;Xiong & Yuan, 2018), type of standard English whether British or American (Lindqvist & Soler, 2022) and the incorporation of moral values (Canh, 2018;Feng, 2019;Puspitasari et al, 2021). Some addressed the idea of promoting critical thinking in listening skills (Irianti et al, 2022), speaking (Viana et al, 2022), and writing skills (Arifin et al, 2020). However, the present study focused on investigating HOTS and LOTS incorporated in the reading section of an EFL textbook.…”
Section: Introductionmentioning
confidence: 97%
“…Some focus on cultural incorporation (Ariawan, 2020;Elmiana, 2019;Setyono & Widodo, 2019), gender representation (Koster & Litosseliti, 2021;Lee, 2018;Sovič & Hus, 2015;Widodo & Elyas, 2020;Yasin et al, 2012), ideology, religion, and identity (Behnam & Mozaheb, 2013;Tran-Thanh, 2020;Vu & Febrianti, 2018;Xiong & Yuan, 2018), type of standard English whether British or American (Lindqvist & Soler, 2022) and the incorporation of moral values (Canh, 2018;Feng, 2019;Puspitasari et al, 2021). Some addressed the idea of promoting critical thinking in listening skills (Irianti et al, 2022), speaking (Viana et al, 2022), and writing skills (Arifin et al, 2020). However, the present study focused on investigating HOTS and LOTS incorporated in the reading section of an EFL textbook.…”
Section: Introductionmentioning
confidence: 97%
“…To speak, confidence is also important for students to have so they can speak the right language. Maulana, Daud and Heriansyah (2016), the problems that students faced in speaking English is their less of confidence to speak and they are afraid of making errors or inaccuracy while speaking besides other problems like their lack of vocabulary and poor pronunciation.…”
Section: Introductionmentioning
confidence: 99%
“…They aim to encourage active participation and critical engagement among students. Furthermore, Utari (2020) andMaulana (2022) found that EFL students face internal and external challenges when it comes to developing satisfactory levels of critical thinking. They emphasized the importance of teaching methods in influencing this process.…”
mentioning
confidence: 99%